Semi-active control of a methalic scalled frame with a MR damper: numerical and experimental research - Braz-César, M.T. (2012)
The need of vibration control has been spreading in tha last two decades to new application fields such as in the dynamic response of civil engineering structures. In this specific field a promising new technology for control of structural vibrations is based on the use of magneto-rheological (MR) fluid devices in the so-called MR dampers. The present work describes part of the R&D on using a semi-active structural control technique in a civil engineering experimental model frame equipped with a MR damper, developed within COVICOCEPAD project approved in the framework of Eurocores program S3T. Some results are provided associated with the calibration of a MR damper at FEUP as well as on the experimental modal indentification of the dynamic properties os a small-scale metallic frame, without and wich inclusion of a specific MR device. Some numerical results of the controlled frame under simulated earthquakes are given, to be later compared with the experimental results of such frame installed in a Quanser shaking table.